2000
DOI: 10.2214/ajr.174.5.1741433
|View full text |Cite
|
Sign up to set email alerts
|

Sonography for Selecting Candidates for Laparoscopic Cholecystectomy

Abstract: OBJECTIVE . We assessed the value of sonography in predicting intraoperative difficulties for patients undergoing laparoscopic cholecystectomy and in identifying indicators for conversion to conventional cholecystectomy. SUBJECTS AND METHODS . Upper abdominal sonography was performed (according to a checklist) in 75 consecutive patients before laparoscopic cholecystectomy. Sonographic findings were verified by the surgeon in the operating room.RESULTS . Conversion from laparoscopic surgery to laparotomy was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
1
19
0
2
Order By: Relevance
“…The identification of parameters predicting conversion helps in preoperative patient counseling, provides for better perioperative planning and avoids laparoscopy associated complications by converting to open procedure as and when appropriate. [12][13][14][15] In our study it has been observed 16 In 1994, Fried, et al published a study suggesting that the most significant predictors of conversion were increasing age, obesity, thickened gallbladder wall by pre-operative ultrasound and acute cholecystitis. Male sex was also one of them.…”
supporting
confidence: 54%
“…The identification of parameters predicting conversion helps in preoperative patient counseling, provides for better perioperative planning and avoids laparoscopy associated complications by converting to open procedure as and when appropriate. [12][13][14][15] In our study it has been observed 16 In 1994, Fried, et al published a study suggesting that the most significant predictors of conversion were increasing age, obesity, thickened gallbladder wall by pre-operative ultrasound and acute cholecystitis. Male sex was also one of them.…”
supporting
confidence: 54%
“…(12) Contracted Gallbladder In our study, we observed that laparoscopic cholecystectomy was difficult in all 7 patients with contracted gallbladder. Though statistically insignificant may be because of small number of cases, contracted gallbladder with thick-walled gallbladder is a strong predictor of difficult laparoscopic cholecystectomy (p value 0.001).…”
Section: Gallstone (Biliary) Pancreatitismentioning
confidence: 59%
“…[18,19] In contrast, study done by Sharma et al found that management of patients by OC was done in up to 45% of patients.. [20] Bingener et al reported managing 5.2% of the patients by open surgery. [21] Ishizaki et al and Gence et al reported managing 7.5% & 3.16% of patients by open surgery respectively. [22,23] The leading cause for management of patients by open surgery was presence of adhesions in our study.…”
Section: Discussionmentioning
confidence: 98%